IDENTIFICATION OF THE STATUS OF RIPARIAN VEGETATION ALONG DADIN KOWA RIVER, YAMATU DEBA LGA, GOMBE STATE, NIGERIA - MUHAMMED BASHIR , BELLO; YARIMA BELLO, MOHAMMED (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2023)
The study ascertained the true status of riparian vegetation along River Gongola basin Dadin-Kowa Dam Area. Both qualitative and quantitative data were used for the study. Remote sensing data was collected where Landsat 7 and 8 imageries (multi date - 1999 and 2019 data were sourced from www.usgs.nasa.gov at 30m resolution. Systematic sampling techniques was adopted for selection of quadrats while the respondents were selected using purposive sampling method. A line transects of 100m X 100m were laid systematically along the river course. On each transect quadrats of 30m X 30m were established for the survey. Microsoft excel, ERDAS software and ArcMap 10.4 GIS software were applied in the analysis. Result from the inventory of floristic composition within river Gongola around Dadin-Kowa Dam area revealed that, there are about 52 species of different genera. Azadirachta Indica was found to be more dominant specie with 790 stands (36.42%), followed by Mangifera indica with 403 stands (18.58%), then Anarcadium occidentale with 196 stands (9.04%). The year 2019 witnessed decline in the phenological characteristics of general vegetation, since 1999 dense vegetation has been decreasing. It has been discovered that, riparian vegetation has been altered by human activities such as farming, grazing, fuel wood collection, fire and establishment of settlements. The vegetation is reduced to isolated trees, leaving large open areas with buildings and open space. Plantation of economic tress such mango, guava, banana and cashew are found along the river bank which is a threat to native species. Species with high relative density (RD) are the most dominants. Anthropogenic disturbances course vegetation change negatively in the study area respectively, it has been concluded that riparian vegetation is decreasing due to impact of human activities around the area hence the need to halt the situation for future sustainability. The study recommended that afforestation programme should enforce and sustained.